2019
DOI: 10.1016/j.jtherbio.2019.102419
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock sensitivity of adult male fertility in the parasitoid wasp Anisopteromalus calandrae (Hymenoptera, Pteromalidae)

Abstract: In insects, decreased reproduction is a sublethal consequence of high temperatures, with males being more sensitive to this in many species. In hymenoptera, arrhenotokous parthenogenesis means that female offspring are produced using sperm and are thus diploid, while males are haploid. Consequently, sperm stocks in males and females (after copulation) are a key regulator of the sex ratio. Anisopteromalus calandrae is a parasitoid wasp in which males can suffer from subfertility due to a drastic decrease in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Together, these studies suggest that there are several time points with heightened temperature sensitivity throughout male reproductive development. Heat shock treatments applied on adults have also been found to decrease numbers of transferred sperm and reduce fertility (Chevrier et al, 2019;Sales et al, 2018Sales et al, , 2021, but considering the data presented here and in Sales et al (2021), such effects may be reversible in most cases. Similar changes in the morphology of female reproductive organs (i.e., smaller ovaries) combined with a strong reduction in egg number have also been reported for flies of the species Drosophila suzukii developing at elevated temperature (Kirk Green et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Together, these studies suggest that there are several time points with heightened temperature sensitivity throughout male reproductive development. Heat shock treatments applied on adults have also been found to decrease numbers of transferred sperm and reduce fertility (Chevrier et al, 2019;Sales et al, 2018Sales et al, , 2021, but considering the data presented here and in Sales et al (2021), such effects may be reversible in most cases. Similar changes in the morphology of female reproductive organs (i.e., smaller ovaries) combined with a strong reduction in egg number have also been reported for flies of the species Drosophila suzukii developing at elevated temperature (Kirk Green et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, thrips productivity appeared to increase with temperature for screen cages, but again, it was only weakly correlated and a drop in productivity was observed in mid-summer. We analyzed mean temperatures over the course of the entire generation for each batch, but it has been shown that temporary and/or repeated exposures to extreme temperatures can impact fitness in other insects [ 35 , 36 ]. This remains for a future study in which the impacts of extremes and their duration of exposure will be quantitatively studied for P. ichini .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the blowfly, Calliphora erythrocephala , egg and early‐stage larvae are less tolerant to heat stress than later developmental stages (Davison, 1969). Thus, in the current context, given spermatogenesis is a protracted process, in which the production of functional sperm during the later stages of development relies on the successful organogenesis of the testes during earlier stages of development, then it is likely the process will be more or less sensitive to temperature stress during different stages of ontogeny (Boivin et al ., 2005; Chevrier et al ., 2019). However, very little is known about the sensitivity of spermatogenesis to thermal stress when applied at the different stages of development.…”
Section: Introductionmentioning
confidence: 99%